SOYBEAN SEEDLING ROOT GROWTH PROMOTION BY 1-AMINOCYCLOPROPANE-1-CARBOXYLATE DEAMINASE-PRODUCING PSEUDOMONADS - Husen, Edi; Wahyudi, Aris Tri; Suwanto, Antonius; Saraswati, Rasti (Indonesian Journal of Agricultural Science, 2009)
Pseudomonad producing 1-aminocyclopropane-1-carboxylate(ACC) deaminase (E.C.4.1.99.4) has been known to promoteplant growth by lowering ethylene biosynthesis in higher plants,which can be induced by indole-3-acetic acid (IAA) production.The objective of this study was to examine the ability of IAAproducingPseudomonas isolated from local soil environment(rhizosphere of soybean grown in Plumbons agricultural areain Cirebon, West Java, Indonesia) to promote soybean root growthin relation to their ACC deaminase activities. The experimentswere conducted in growth room and Laboratory of Soil BiologyResearch, Indonesian Soil Research Institute, Bogor, from Januaryto August 2008. Soybean seeds were inoculated by immersing theseeds for 1 hour in bacterial cell suspension containingapproximately 108-109 cells ml-1. The seeds were then germinatedfor 2 days before planting in growth pouches containing sterilizeddistilled water. All treated and untreated seeds were grown for7 days in growth room at 24Â°C with 1300 lux of light intensityfor 12-hour followed by a 12-hour dark period at 22Â°C. ACCdeaminase activity of the isolates was assayed based on their abilityto grow in Dworkin-Fosterâs salt minimal medium containingammonium sulfate or ACC as a source of nitrogen. Thirteen outof 81 isolates tested significantly increased soybean root lengthand weight, up to 50% from untreated plants. Of 13 isolates,11 demonstrated ACC deaminase activities. Two isolates thatdid not show ACC deaminase activities had lower capacity toproduce IAA. The results suggest that the effectiveness of IAAproducingPseudomonas in promoting the growth of the soybeanseedlings is associated with their ACC deaminase activities orthey produce IAA at low levels.